Administrative Guidelines for the One-Baht-Per-Day Community Welfare Fund in Kotabaru Subdistrict Municipality, Raman District, Yala Province, Thailand - เจ๊ะอาแม, ไซฟูล; แซเมาะ, กอนานู; ตาตอเละ, อาฟีซี; สุขเสนีย์, คมวิทย์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research aimed to examine the management process of the One-Baht-Per-Day Welfare Fund and to investigate the problems and obstacles in its management. The study employed a qualitative research approach. The key informants consisted of 15 participants, including four chairpersons and vice-chairpersons of the fund group, five committee members, five fund members, and the mayor of Kota Baru Subdistrict Municipality. The informants were selected through purposive sampling based on their roles and direct experience related to fund management. The research instrument was a semi-structured interview guide. Data were collected through in-depth interviews and focus group discussions and were analyzed using content analysis. The findings revealed that the fund management process consisted of eight stages: initiating ideas and building mutual understanding; identifying and utilizing community potential and capital; expanding and developing core leaders; coordinating with local agencies; establishing the community welfare fund; participatory fund management; monitoring and evaluation; and expansion and development toward sustainability. The problems and obstacles in fund management were identified in four aspects: personnel, budget, management, and materials and equipment. The findings can serve as empirical evidence for policy formulation, planning, and the development of fund management guidelines in accordance with the needs of people in the area.